A multisciplinary approach to the study and conservation of the contemporary Sarah Lucas’ papier-maché sculpture Love Me - Fabiola Rocco (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The thesis project concerned the interdisciplinary study and the conservation treatment of Sarah Lucas’ papier-mâché sculpture Love Me, owned by the Sandretto Re Rebaudengo Foundation (Turin). The sculpture suffered mainly from structural damages caused by external factors such as several transports, ingrained surface dirt and previous conservation treatments made with inappropriate materials. The dialogue with the artist was necessary and helpful to understand the artist’s intention and the meaning of the oeuvre, in order to perform a conscious conservation treatment.